A childhood in Tibet : Tendöl's story - Obrecht, Thérèse (Gurugram, Haryana, India : Penguin Viking, 2021)
"Tendöl Namling turned 62 in March 2021. She was born when the Dalai Lama fled from Lhasa and the uprising of his people was brutally suppressed by the Chinese People's Liberation Army. She lived for 22 years under Chinese rule. As the daughter of a high-ranking government official, she underwent the ordeal of re-education with full force. All that is left of those years are painful memories and some crumpled photographs. They show her with her friends and cousins in Lhasa, smiling as if nothing had happened. When Tendöl turned 10 her brother was arrested and her mother sentenced to ten years in prison. Tendöl was sent to work in road construction for several years. At the age of 20 she was allowed to start an apprenticeship as a motor mechanic. Thanks to the efforts of her family in exile, Tendöl was able to leave Tibet in 1982. After twenty-two years of hardship, she landed in prosperous Switzerland. It was as though she had to start her life all over again. She struggled, but she never gave up. She built a family and a business and reconciled herself with the painful past."--Dust jacket.
First published in Switzerland in 2019.
Keywords: Namling, Tendöl.; Tibetans -- Biography; Tibetans -- Switzerland -- Biography; Tibet Autonomous Region (China) -- Biography; Tibétains -- Biographies; Région autonome du Tibet (Chine) -- Biographies; Tibetans; China -- Tibet Autonomous Region; Switzerland; collective biographies; Biographies; Biographies; Biographies